Dental effects of enzyme replacement therapy in case of childhood-type hypophosphatasia - Rena Okawa; Kazuma Kokomoto; Kazuhiko Nakano (BMC, 2021)
Abstract Background Hypophosphatasia (HPP), a skeletal disease characterized by hypomineralization of bone and teeth, is caused by an ALPL gene mutation that leads to low activity of the tissue non-specific alkaline phosphatase enzyme. Although enzyme replacement therapy (ERT) was recently introduced for affected patients, no known studies have been reported regarding its dental effects related to permanent teeth and jaw bones. In the present study, we examined the dental effects of ERT in a case of childhood-type hypophosphatasia, including panoramic radiography findings used to estimate the dental age of permanent teeth and mandibular bone density. Furthermore, the effects of that therapy on the periodontal condition of the patient were evaluated by comparing periodontal pocket depth before and after initiation. Case presentation An 11-year-1-month-old boy was referred to our clinic for consultation regarding oral management. Two primary incisors had spontaneously exfoliated at 1 year 8 months old and he had been diagnosed with childhood-type HPP at the age of 2 years 2 months. Obvious symptoms were localized in the dental region at the time of diagnosis, though later extended to other parts of the body such as bone pain. ERT was started at 11 years 7 months of age, after which bone pain disappeared, and motor functions and activities of daily living improved. We estimated dental age based on tooth development stage. The age gap between chronological and dental ages was expanded before treatment, and then showed a constant decrease after ERT initiation and finally disappeared. The index for mandibular bone density (mandibular cortical width / length from mesial buccal cusp to apex of first molar) was increased after ERT initiation. Furthermore, the periodontal condition for all teeth except those exfoliated was stable after starting therapy. Conclusions ERT resulted in improved tooth and mandibular bone mineralization, with notably good effects on teeth under formation. Acceleration of mineralization of roots associated with erupting teeth leads to stabilization of the periodontal condition. We concluded that ERT contributed to the improved dental condition seen in this patient.